Pelatihan Dan Pendampingan Instalasi Jaringan Internet Untuk Peningkatan Pelayanan Pada Kantor Desa - Harianto, Harianto; Aris Sudianto; Muhammad Wasil; Muhamad Sadali; Baiq Andriska Candra Permana; Mahpuz; Suhartini; Hamzan Ahmadi; Indra Gunawan; Imam Fathurrahman; Lalu Kertawijaya; Ida Wahidah; Jumawal; Muhammad Djamaluddin (Jurnal Teknologi Informasi untuk Masyarakat, 2024)
Abstract: The Village Office is a government agency that is directly connected or interacts with the community. The community is the object that will be served by Village officials. It is not uncommon for people to feel dissatisfied with slow service. One of the community satisfaction with the performance of Village staff is the provision of fast and appropriate service. One way to increase village service staff to the community must be supported by adequate devices and equipment, especially for accessing and sharing data or information both locally and on the internet. To make this happen, you must have knowledge and skills in the field of networking. Therefore, socialization, training and assistance with internet network installation are needed. It is hoped that this will help the Village, especially staff, to increase their knowledge and skills in the field of networking, so that they can improve services to the community more quickly and precisely. Keywords: Internet Network, Village Office Staff, Community, Services.